2017
DOI: 10.1039/c7nr06359h
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of water-soluble silver nanoclusters: superstructure formation and morphological evolution

Abstract: Supramolecular self-assembly, based on non-covalent interactions, has been employed as an efficient approach to obtain various functional materials from nanometer-sized building blocks, in particular, [Ag(mna)], mna = mercaptonicotinate (Ag-NC). A challenging issue is how to modulate the self-assembly process through regulating the relationship between building blocks and solvents. Herein, we report the controlled self-assembly of hexanuclear silver nanoclusters into robust multilayer vesicles in different sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 55 publications
1
37
0
1
Order By: Relevance
“…It is known that, for amphiphilic molecules, adding a poor solvent to a miscible, good solvent, in which the solute dissolved, could easily trigger the formation of aggregates . As is reported in our previous study, water is a good solvent for Ag 6 ‐NCs as they can not self‐assemble in water, whereas DMSO is a poor solvent for Ag 6 ‐NCs. Thus, firstly, the self‐assembly behaviors of Ag 6 ‐NCs in the mixed solvents were studied.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…It is known that, for amphiphilic molecules, adding a poor solvent to a miscible, good solvent, in which the solute dissolved, could easily trigger the formation of aggregates . As is reported in our previous study, water is a good solvent for Ag 6 ‐NCs as they can not self‐assemble in water, whereas DMSO is a poor solvent for Ag 6 ‐NCs. Thus, firstly, the self‐assembly behaviors of Ag 6 ‐NCs in the mixed solvents were studied.…”
Section: Resultssupporting
confidence: 56%
“…Synthesis of Ag 6 -NCs and Ag 6 @C 16 mim-NCs Ag 6 -NCs were synthesized according to our published procedure. [29] Ag 6 @C 16 mim-NCs were synthesized as follows:C 16 mimBr solution (3 mL, c = 20 mmol L À1 )w as added into Ag 6 -NCs solution (10 mL, c = 1mmol L À1 ), which caused precipitates to form. After 1h,t he reaction was nearly complete.…”
Section: Experiments Sectionmentioning
confidence: 99%
“…Manipulating the self-assembly of Ag NCs based on non-covalent forces through modulating the interactions between building blocks and solvents. Shen et al reported the controlled assembly of mercaptonicotinate (MNA)-capped Ag NCs into multilayer vesicles or nanowires in different solvents [46]. After protonating the Ag NCs by adding hydrochloric acid, the morphology of self-assembled vesicles kept stable in aprotic solvents, such as DMSO and CH 3 CN, while in protic solvents, such as water, MeOH, and EG, the vesicular morphology would transform into nanowires (Figure 6).…”
Section: The Self-assembly Of Ag Ncsmentioning
confidence: 99%
“…Moreover, the MOGs are quite stable without noticeable changes for months at room temperature. This high colloidal stability, together with the regular morphology and high order of the self‐assemblies, make current system an important supplement to existed metal NC‐based AIE systems and metal NC‐based gels . The MOGs are formed solely by Ag 9 NCs without the assistance of any organic gelator, indicating a high content of the metal NCs in MOGs.…”
Section: Figurementioning
confidence: 99%